CYBER SCHOOL SMK PGRI 1 KOTA TANGERANG - Didi Kurnaedi (PROSIDING SNAST, 2018)
SMK PGRI 1 Tangerang is a school under the auspices of the Indonesian Teachers Association (PGRI), supported by the power of information and communication technology. Information Technology has changed the learning method both for students and teachers, as an alternative learning SMK PGRI 1 Tangerang City to manage learning with the concept of Cyber ​​School. The concept of Cyber ​​School is a school-based concept of technology in the process of teaching and learning in the classroom. Utilization of information technology includes an integrated system that helps the education community in carrying out their respective functions with the aim of developing the potential of learners. One technology that is often used in teaching and learning is the use of Internet-based or Web-based technologies. the use of technology in the field of education is to help the learning process and improve performance by making, using, and managing processes and sources of technology adequate This research uses a qualitative approach. The subject of research is SMK PGRI 1 Kota Tangerang. This research includes qualitative research with descriptive approach. Technique of taking data through observation, interview and documentation. In order for the results of research to run well, then the process of data analysis is done by the following steps: first, data reduction, second presentation of data and third, verification is the conclusion that provides analysis. Concept Cyber ​​School SMK PGRI 1 Tangerang has modules admistarsi, academic modules, and supervisory module, Cyber School can assist principals in monitoring the events occurring in schools